Sound model of an acoustic improved air to water heat pump - Schmidt Thorsten; Müller Dirk (Acta Acustica)
Heat pumps represent an essential component of the energy transition. While they are effective in generating heat, they also generate sound, which has the potential to cause annoyance. Therefore, it is essential to enhance the transparency of the sound behavior. Analyses were performed to identify the factors that influence sound levels at the component and system levels. A total of three refrigerant compressors were examined with the objective of determining the most acoustically efficient components currently available and the key factors influencing acoustics. Two low-noise axial fans are used to illustrate the differing sound characteristics when used in a heat pump application. Based on component tests and measurements at the heat pump system level, the speeds of the compressor and fan were confirmed as significant factors influencing the sound emissions of air-to-water heat pumps. In addition, the flow temperature and the operating point of the fan were identified as factors influencing. The results were employed to develop an acoustically improved heat pump demonstrator, which was based on a representative design. A sound model could be developed that is capable of describing the sound behavior for a wide range of operating conditions. This methodology allows for increased transparency in sound behavior. Different sound behaviors of heat pumps can be demonstrated on the basis of the model, and discussions on the definition of maximum sound specifications can be held on the basis of data. Sound emissions should not only be linked to heat output, as this increases the uncertainty of comparability. A transparent representation of the speeds is strongly recommended.